O estágio supervisionado em licenciaturas: a concepção de professores orientadores sobre a dimensão da prática - Gouveia, Rebeca Leitão (2022)
The Supervised Internship (SI), a mandatory subject in the curriculum of Licentiate courses, is the space that inserts students into their future workplace, the school environment, in order to make it possible to know the demands of the school reality and to approach the reality in which they will act as teachers. By providing this insertion, it is undeniable that in comparison with the other disciplines of the Licentiate courses, SI carries the status of “practical discipline of the course”; however, the nature of this practice needs to be understood, which led to the development of the present research. When considering the teacher as a historically and socially constructed subject, his conception of the world constitutes one of the elements in the construction of the discipline he teaches. Therefore, the conception of practice of the teaching advisor of him also influences the way in which he guides the discipline. In this sense, the present research aims to understand the practice conception of the supervisors of Supervised Internship studies in the Licentiate courses at UFPB, in the perspective of the theory and practice dialectic. The research has as its theoretical-methodological foundation the historicaldialectical materialism, which, through the dialectical movement, allows to know the totality and the essence of the object of this study in its relations and contradictions, placing it in its historical context. The qualitative research investigated the conception of practice of 8 (eight) professors who teach the subject SI on Teaching Degrees, using the semi-structured interview as an instrument for collecting information. Despite the different perspectives of practice presented in Licentiate courses, it is believed that it is impossible to analyse practice without considering theory, that is, without considering the dialectical relationship of unity and contradiction between theory and practice and, consequently, as a transformation of man and social nature, in short, as praxis. The present study makes it possible to highlight that the conception of practice on SI is mainly guided by the Epistemology of Practice, even if the professor is not aware of this approach, since SI is evidenced as the moment of individual and fragmented practice, with theories having a utilitarian character in this field, and the school as an essentially practical space.